2014
DOI: 10.1002/jso.23553
|View full text |Cite
|
Sign up to set email alerts
|

Isolated limb infusion with melphalan and actinomycin D for melanoma: A systematic review

Abstract: Isolated limb infusion (ILI) was developed as a simplified and minimally invasive alternative to isolated limb perfusion (ILP) to treat unresectable limb melanoma. A number of centers around the world have reported their results using this procedure. In this study a systematic review of reported ILI experiences was undertaken. A literature search was conducted according to the guidelines for systematic reviews in order to select eligible papers reporting limb toxicity and response rates following ILI using mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…168,[170][171][172][173][174] An analysis of 7 studies involving 576 patients, primarily with stage III disease and treated with melphalan/actinomycin D combination via ILI, showed an overall response rate of 73%, with complete response in 33% (range, 26%-44% across studies), partial response in 40% (33%-53%), and stable disease in 14%. 167 A smaller pooled analysis of 2 additional studies (N=58), one a noncomparative phase II study (ClinicalTrials.gov identifier: NCT00004250), showed similar overall response rates for stage IIIB versus stage IIIC disease (48% vs 40%), and similar 5-year survival rates (38% vs 52%). 175 Complete responses were achieved in 25% of patients, partial responses in 20%.…”
Section: Regional Therapy: Isolated Limb Perfusion and Infusionmentioning
confidence: 98%
See 1 more Smart Citation
“…168,[170][171][172][173][174] An analysis of 7 studies involving 576 patients, primarily with stage III disease and treated with melphalan/actinomycin D combination via ILI, showed an overall response rate of 73%, with complete response in 33% (range, 26%-44% across studies), partial response in 40% (33%-53%), and stable disease in 14%. 167 A smaller pooled analysis of 2 additional studies (N=58), one a noncomparative phase II study (ClinicalTrials.gov identifier: NCT00004250), showed similar overall response rates for stage IIIB versus stage IIIC disease (48% vs 40%), and similar 5-year survival rates (38% vs 52%). 175 Complete responses were achieved in 25% of patients, partial responses in 20%.…”
Section: Regional Therapy: Isolated Limb Perfusion and Infusionmentioning
confidence: 98%
“…166 Melphalan is commonly used for ILI, often with actinomycin D. 167 The addition of papaverine for cutaneous vasodilation has been shown to increase response rate but also the risk of regional toxicity. 168,169 ILI is associated with lower rates of toxicity and morbidity compared with ILP, but retrospective comparisons of response and survival with ILP versus ILI have shown varying results.…”
Section: Regional Therapy: Isolated Limb Perfusion and Infusionmentioning
confidence: 99%
“…13 These data showed that the effect of HuR-regulated APP and ADAM10 F I G U R E 1 EGCG reduces the expression of APP and ADAM10 via regulation of HuR in tumour cells. Transiently transfected with HuR plasmids in tumour cells obviously eliminated the effect of EGCG-down-regulated expression of APP and ADAM10.…”
Section: Discussionmentioning
confidence: 85%
“…Unexpectedly, the decrease rate of APP and ADAM10 has no difference between the experiment group and control group in tumour cell treatment with actinomycin D which was used to inhibit de novo transcription. 13 These data showed that the effect of HuR-regulated APP and ADAM10 As Erk1/2 plays a key role in cell apoptosis and APP regulation, 14,15 we hypothesized that HuR regulated APP and ADAM10 level through Erk1/2 signalling pathway. Indeed, HuR enhanced the phosphorylation of Erk1/2 in tumour cells.…”
Section: Discussionmentioning
confidence: 93%
“…4 ILI has been extensively investigated for unresectable recurrent melanoma within large, randomized prospective studies. [5][6][7] Complete and partial response (PR) rates have been consistently reported between 24% to 38% and 22% to 40%, respectively, with median overall survival (OS) periods of up to 44 months. 8,9 Predictors of response to ILI using local data have also been described by Barbour et al 10 More recently, intralesional Rose Bengal (PV-10) has been studied for locoregionally advanced and metastatic melanoma.…”
mentioning
confidence: 99%